2010
DOI: 10.1007/s00430-010-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Monoassociation with probiotic Lactobacillus delbrueckii UFV-H2b20 stimulates the immune system and protects germfree mice against Listeria monocytogenes infection

Abstract: In the present study, we investigated the protective effects of Lactobacillus delbrueckii UFV-H2b20 on the resistance to Listeria monocytogenes infection in gnotobiotic mice. Germfree mice or monoassociated mice were infected with L. monocytogenes, and the microbiological and immunological responses were evaluated after 1, 3, and 5 days of infection. Monoassociation with L. delbrueckii was capable of protecting mice against death caused by L. monocytogenes and induced a faster clearance of the bacteria in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
0
40
0
2
Order By: Relevance
“…Work published as early as 1979 revealed that GF animals show increased susceptibility to Lm colonization and that the intestinal microbiota, introduced either individually or as a community, is capable of decreasing Lm colonization of GF mice (Archambaud et al, 2012; Bambirra et al, 2007; dos Santos et al, 2011; Nakamura et al, 2012; Vieira et al, 2008; Zachar & Savage, 1979) and rats (Czuprynski & Balish, 1981). Although these studies do not provide clear mechanisms for colonization resistance, they nevertheless demonstrate a functional requirement for the gut microbiota in protection against L. monocytogenes infection.…”
Section: Virulence Regulation Of Enteric Pathogens By Scfamentioning
confidence: 99%
“…Work published as early as 1979 revealed that GF animals show increased susceptibility to Lm colonization and that the intestinal microbiota, introduced either individually or as a community, is capable of decreasing Lm colonization of GF mice (Archambaud et al, 2012; Bambirra et al, 2007; dos Santos et al, 2011; Nakamura et al, 2012; Vieira et al, 2008; Zachar & Savage, 1979) and rats (Czuprynski & Balish, 1981). Although these studies do not provide clear mechanisms for colonization resistance, they nevertheless demonstrate a functional requirement for the gut microbiota in protection against L. monocytogenes infection.…”
Section: Virulence Regulation Of Enteric Pathogens By Scfamentioning
confidence: 99%
“…Indeed, studies have found that GF mice are more susceptible to infection by Leishmania major (39) or Trypanosoma cruzi (40). In addition, infection by the Gram‐positive intracellular pathogen Listeria monocytogenes resulted in decreased bacterial clearance in GF animals compared with colonized animals (41). We have also found that there is limited production of TNF‐α and CXCL‐1 and reduction of neutrophil influx after pulmonary infection with Klebsiella pneumoniae (Fagundes, Teixeira, and Souza, unpublished data).…”
Section: Regulation Of Inflammatory Responsiveness By the Microbiotamentioning
confidence: 99%
“…Lactobacillus delbrueckii on the other hand is a pronounced dairy starter culture recently reported for its probiotic traits and immunological effects in vivo (Dos Santos et al . ; Santos et al . ; Archer et al .…”
Section: Introductionmentioning
confidence: 99%